Patterns of Enculturation of Keroncong Music in Worship (Case Study at Gereja Sidang Jemaat Allah Malang) - Susanti, Lidia; Suseno, Aji; Hamzah, Amir (BIA': Jurnal Teologi dan Pendidikan Kristen Kontekstual, 2023)
Abstract: This study attempts to identify patterns of enculturation of keroncong music in Malang's Maranatha Congregational Church. Utilizing exploratory exposure patterns and instrumental case studies, the research method employs case studies as a research tool. The research identified three patterns of enculturation of keroncong music in Malang's Maranatha Assembly Church: conservative, moderate, and transformative. These three patterns can be utilized effectively and potentially if the following conditions are met: (1) Keroncong music can make a church more authentic if it can serve as a unifying force for the congregation; however, it can also be used to incite conflict. (2) Good arrangement skills are required to combine popular church music with keroncong music, and (3) In addition to the completeness of digital musical instruments, the completeness of instruments and scores of original keroncong music is required to accommodate the playing style of teenagers. (4) There is a need for mutual understanding and respect for the opinions of different groups within the church, as well as the ability to find solutions that are conducive to solving each problem; and (5) An adequate and balanced management plan is required to accommodate every thought and need of each group within the church so that they can exercise their rights and responsibilities in a reasonable manner.Â Keywords: Enculturation, keroncong music, worship